Metacognitive Language Learning Integrated with Linguistic Awareness in Improving EFL Learners’ Reading Comprehension - Tri Setianingsih; Baiq Zohratun Nafisah; Sadaff Hamaros (Journal of Linguistic Metacognition and Language Learning, 2026)
This study investigates the integration of metacognitive strategies and linguistic awareness in enhancing reading comprehension among English as a Foreign Language (EFL) learners. Metacognitive strategies, such as self-regulation, goal-setting, and reflection, have been shown to improve learners' ability to monitor their understanding of texts, while linguistic awareness—encompassing phonological, morphological, and syntactic knowledge—enables learners to process and decode complex language structures. The research adopts a qualitative design, with data collected through semi-structured interviews and classroom observations of ten certified EFL teachers in Indonesia. The participants, each with 5-10 years of teaching experience, shared their insights on how these strategies were implemented in the classroom to support reading comprehension. The study found that the combination of metacognitive strategies and linguistic awareness significantly enhanced learners' reading comprehension. Teachers reported that students who actively used metacognitive strategies were better able to identify comprehension gaps and apply corrective strategies, such as re-reading or summarizing, to improve understanding. Additionally, linguistic awareness facilitated learners' ability to decode vocabulary and understand sentence structures, contributing to greater fluency and accuracy in reading. The research highlights the importance of integrating both metacognitive and linguistic elements into EFL instruction to provide a holistic approach to language learning. These findings offer valuable insights for educators seeking to improve their teaching practices and enhance the reading comprehension skills of their students. The study concludes with recommendations for further research and professional development in integrating these strategies into EFL classrooms.